Prevalence and Risk Factors of Anemia in Adolescent Girls in Donggala District, Central Sulawesi - Amsal, Amsal; Subagyo, Indro; Taqwin, Taqwin; Kusumawati, Dwi Erma; Radhiah, Sitti; Eka Cahyani, Yayuk; Hafid, Fahmi (Poltekkes Kemenkes Palu, 2023)
This study aims to assess the prevalence and risk factors of anemia in adolescent girls in Donggala District. It employed an observational analytical study design with a cross-sectional approach. The research was conducted in Senior High Schools (SMA) and Islamic Senior High Schools (Madrasah Aliyah) in Donggala District in May 2023. The sample included 428 respondents. Hemoglobin levels were measured by the laboratory staff of the Central Sulawesi Health Department. Respondents provided data through Kobocollect: https://ee.kobotoolbox.org/x/uZVqfjnh. Respondent characteristics included age, the occupation of both parents, family income, upper arm circumference, hemoglobin levels, body mass index, menstrual status, consumption of iron supplements, anemia education and knowledge, medical conditions, smoking status, physical activity status, and the frequency of iron-rich food intake (fish, eggs, meat, and milk). Data analysis was performed using percentages and RR (95% CI) with SPSS 22.0. Ethical approval was obtained from the Ethics Committee of the Poltekkes Kemenkes Palu with approval number 0016/KEPK-KPK/I/2023, and research permission was granted by the Central Sulawesi Provincial Government, Regional Unity of Community and Political Affairs, with approval number 070/0409/Bid.III-BKBPD/2023. The research results indicated a prevalence of anemia risk among adolescents in Donggala District at 9.8%. Risk factors included upper arm circumference <23.5 cm, a history of kidney disease, limited knowledge of anemia, and infrequent meat consumption. The researchers recommend that adolescents increase their food intake to improve upper arm circumference, manage dietary patterns for those with kidney disease, enhance knowledge about anemia, and increase meat consumption frequency.